Portrait of Environmental Governance in Waste Management in Malang City - Rosyidatuzzahro Anisykurlillah; Stefanus Sampe (Jurnal Ilmu Lingkungan, 2024)
The government has set the main national targets for waste management, namely 30% waste reduction and 70% waste handling by 2025. However, waste generation in Malang City continues to increase yearly and is included in the high category in East Java. This study aims to analyze waste management in Malang City from an environmental governance perspective. The environmental governance perspective can be analyzed using Belbase's theory with seven indicators of good environmental governance, namely 1. the rule of law, 2. participation and representation, 3. access to information, 4. transparency and accountability, 5 decentralization, 6. institutions and institutions, 7. access to justice. Data collection was carried out using interviews, observation, and literature study. The data analysis used in this study is the interactive model analysis of Miles, Huberman, and Saldana. The portrait of environmental governance in Malang City waste management must fully reflect the principles of good environmental governance. This is because there are still records in the indicators of the rule of law, participation, and representation, as well as institutions and institutions. Constraints faced in waste management in Malang City include needing to be fully implemented, not yet maximal public awareness in reducing and sorting household waste, as well as institutions and institutions that could be more optimal in waste management.